BONDE DO CINE: UMA EXPERIÊNCIA INTERSETORIAL DE EDUCAÇÃO POPULAR EM SAÚDE. - Dutra Ferrugem, Renata; Samara Funk, Camila; Schwantes de Souza, Renyelle; Santos Machry, Denise; Coelho de Souza, Camila (Revista de Atencao Primaria a Saude)
This report deals with an experience entitled Cine Bevy: discussing cinema, producing health. The project was developed by contracted professionals and residents of a Conceição Hospital Group health unit, located in Vila Jardim - northern district of the city of Porto Alegre, RS - with adolescents from a public school in the same community. This initiative was guided by the principle of Popular Education in Health, trying to join different areas of knowledge and social sectors, in order to contribute to the strengthening, autonomy, and empowerment of adolescents living in the Vila Jardim community. Culture was the common thread of the project, being worked on through videos watched and discussed collectively, based on themes of interest to the teenagers. Project results are positive from the perspective of the different individuals involved, bringing out the challenge of intersectoriality in the construction of common policies and actions for the benefit of the community.